2017
DOI: 10.1177/1179066017695239
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report: Ovarian Sertoli-Leydig Cell Tumor With Hyperestrogenism and Endometrial Hyperplasia in a Postmenopausal Woman

Abstract: The patient was a 66-year-old woman, G2P2. The patient presented a chief complaint of irregular postmenopausal bleeding 1 month ago. A transvaginal ultrasonography showed that bilateral ovaries were not enlarged and uterine endometrium was thickened, measuring at 9 mm. As a result of endometrial curettage, the simple endometrial hyperplasia was revealed. A blood examination showed an elevated estradiol level of 67 pg/mL, an elevated level of testosterone 0.64 ng/mL, and a slightly suppressed follicle-stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…Around 50% of SLCT cases come to clinical attention due to the latter manifestations of progressive masculinisation,4 as was seen in our patient. It has been reported that when the value of testosterone, mainly secreted by the Leydig cells of the tumour, exceeds 2 ng/mL, there is obvious evidence of virilisation 7. Our patient presented with initial total testosterone values as high as 1307 ng/mL, thus explaining many of her signs and symptoms of increased androgens.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Around 50% of SLCT cases come to clinical attention due to the latter manifestations of progressive masculinisation,4 as was seen in our patient. It has been reported that when the value of testosterone, mainly secreted by the Leydig cells of the tumour, exceeds 2 ng/mL, there is obvious evidence of virilisation 7. Our patient presented with initial total testosterone values as high as 1307 ng/mL, thus explaining many of her signs and symptoms of increased androgens.…”
Section: Discussionmentioning
confidence: 59%
“…These tumours are composed of a mixture of cells that morphologically resemble male Sertoli and Leydig cells and are found to be unilateral in 98% of patients 7 8. They mainly secrete testosterone, which can cause endocrine manifestations—seen in about half of the patients—of virilisation to appear 7. The clinical characteristics of SLCT have been found to be associated with the degree of histological differentiation,5 and these clinical signs and symptoms include that of defeminisation (amenorrhoea, oligomenorrhoea and breast atrophy) followed by that of progressive masculinisation (acne, deepening of the voice, hirsutism, temporal balding and clitoromegaly) 5 9.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations